Barriers to effective vitamin D supplementation during ante-natal care. (4th April 2011) - Ling, R E; Coren, M; Goldring, S
Abstract : Aims: Vitamin D deficiency in childhood is a common and recognised public health issue. National guidance recommends that all women should take 10 mcg vitamin D supplements daily during pregnancy and until their child is fully weaned, and midwives should offer this advice at the booking appointment. Two recent severe cases of vitamin D deficiency in infancy presented to our hospital, one with cardiac arrest secondary to hypocalcaemia and one with cardiomyopathy, illustrating the importance of such public health guidance. This study aimed to evaluate the knowledge, practice and barriers to implementation of vitamin D supplementation among midwives. Methods: Quantitative and qualitative methods were used to assess midwife practice in three inner-city hospital-based maternity units. This included an electronic survey and one-to-one interviews which used the critical incident technique. Interviews were structured to elucidate the barriers to offering advice on vitamin D and potential ways to overcome them. Results: 53 of 200 midwives responded to the electronic survey. 21/53 correctly identified the recommended amount of daily vitamin D supplements and 17/53 the duration of supplementation. The number of midwives identifying groups at particular risk where: pigmented skin types (44/53), conservative Islamic dress (48/53), limited sunlight exposure (42/53) and obesity (4/53). 12/53 routinely advised women to take vitamin D supplements. When asked to choose which professionals should offer vitamin D supplementation advice during pregnancy: midwives (36/53), GPs (23/53), and obstetricians (28/53). 40 qualitative interviews identified barriers: not a high-profile topic (25/40), lack of patient information sheet (18/40), time pressure (13/40), 10/40 language barrier (10/40), only needed if vitamin D deficient (3/40) and none (1/40). Suggested improvements were training (26/40), Trust guidelines (9/40), Info Sheets/Posters (21/40), Booking clinic supplies of vitamin D (7/40) and GPs to advise when pregnancy diagnosed (3/40). Conclusion: Implementation of national guidance during pregnancy is essential for promoting optimum child health. Barriers identified by midwives include: the lack of profile of the topic, time pressures and the language barrier with high risk women. To address this targeted education and training for midwives alongside information, in high-risk languages for women should be available.